2020
DOI: 10.1016/j.semperi.2020.151282
|View full text |Cite
|
Sign up to set email alerts
|

Care of the COVID-19 exposed complex newborn infant

Abstract: As we confront COVID-19, the global public health emergency of our times, new knowledge is emerging that, combined with information from prior epidemics, can provide insights on how to manage this threat in specific patient populations. Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS), both caused by coronaviruses, caused serious respiratory illness in pregnant women that resulted in adverse perinatal outcomes. Thus far, COVID-19 appears to follow a mild course in the vast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
(81 reference statements)
1
10
1
2
Order By: Relevance
“…13 By and large there is lack of data on vertical transmission. 14 In present study there was no COVID positive neonate.…”
Section: Discussioncontrasting
confidence: 43%
“…13 By and large there is lack of data on vertical transmission. 14 In present study there was no COVID positive neonate.…”
Section: Discussioncontrasting
confidence: 43%
“…A total of 21 papers describe the regulation of contact between infants and mothers who are infected with COVID-19 or at risk of COVID-19. The types of interventions recommended by previous authors include avoiding skin-to-skin contact [ 56 , 138 142 ], isolation of infants in negative pressure incubators [ 60 , 67 , 111 , 143 , 144 ] or isolation separately from the mother for 14 days [ 55 , 77 , 111 , 120 , 138 , 140 ], rooming-in provision [ 61 , 68 , 147 ], and wear a face mask when breastfeeding or in close contact with infants [ 55 – 59 , 62 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of vertical transmission of SARS-COV-2 from mother to fetus via placenta or caesarean section delivery or vaginal delivery in this study similar to other studies reported. 13,14 None of the literature has detected virus in cord blood, placenta or breast milk. 14 Till date no complication related to steroid use have been reported in mother or infant, but their safety still needs more data to draw conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 None of the literature has detected virus in cord blood, placenta or breast milk. 14 Till date no complication related to steroid use have been reported in mother or infant, but their safety still needs more data to draw conclusion.…”
Section: Discussionmentioning
confidence: 99%